Determinan Kinerja Maqashid Syariah dengan Corporate Governance sebagai Variabel Moderasi Pada Bank Umum Syariah di Indonesia - Raudlatul Izzah; I Gusti Ayu Purnamawati; Gede Adi Yuniarta (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
ABSTRACTWith the Covid-19 pandemic, Islamic banking has quite a lot of challenges, so with this Islamic banking must be able to target problems that arise and then turn them into opportunities to be better. This study aims to examine and analyze the influence of Islamic intellectual capital, Islamic performance index, Islamic corporate social responsibility on the performance of Islamic maqashid and examine and analyze the effect of IIC, IPI, ICSR moderated by corporate governance on the performance of Islamic maqashid in Islamic banks in Indonesia. The population in this study were all registered Islamic banking in Indonesia. The sample in this study is the financial statements and annual reports of Islamic banking registered in Indonesia. While the sampling technique uses a saturated sample technique, which means that the entire population is a sample. The analytical method used is MRA using SPSS 22. This research uses Resource Based Theory. The results of this study indicate that IIC and ICSR have a significant positive effect on the performance of maqashid sharia, IPI does not have a significant positive effect on the performance of maqashid sharia. Corporate governance is able to moderate IIC and ICSR on the performance of maqashid sharia, while corporate governance has not been able to moderate IPI on the performance of maqashid sharia. Keywords: IIC, IPI, ICSR, CG, and Maqashid Sharia Performance